Fast electron transfer processes in cytochrome C and related metalloproteins. - Simic, M G (1978)
Various free radicals formed on pulse radiolysis of aqueous solutions have been used to investigate the mechanisms of reduction of cytochrome(III) c by inter- and intramolecular electron transfer. The rapid formation of free radicals (t less than 1 mus) and their high reactivity with cytochrome (k approximately 10(8)(-5) x 10(10)M(-1)s(-1)) make such studies feasible. Reduction of cytochrome by free radicls is monitored by optical methods. Fast optical changes in the 1(-500)-mus region correspond to reduction of the iron center; whereas the slower changes in the 10(-500)-ms region are attributed to postreduction conformational changes. It has been concluded that the reduction path is mediated through the crevice and that no reduction intermediates are being formed.